Proyek Percontohan Pemberdayaan Ekonomi Umat Melalui Wakaf Produktif Di Era Khalifah Usman Bin Affan - Dimas Dwi Susetyo; Desi Suheni (IAIN Langsa, 2022)
Waqf is one of the Islamic social instruments that is closely related to the socio-economic community. In Indonesia, waqf not only plays a role and function in the side of worship, but waqf is expected to help the economy of the people. Waqf in Indonesia is regulated by Law No. 41 of 2004 has been implemented in a number of community empowerment programs. The Indonesian Ulama Council has legalized this productive waqf in cash waqf, this has enabled the public to donate their money to the institution or organization of the waqf body. Other problems faced in the development of waqf in Indonesia are the development of waqf resource management, a lack of professionalism, commitment and understanding of productive waqf. The stagnation of productive waqf in Indonesia needs special attention from the government and sharia economic activists, where for the development of productive waqf that has existed long ago during the time of Khalifah Usman Bin Affan r.a so that this can become a pilot project for the development of productive waqf in Indonesia.